ASPP proteins specifically stimulate the apoptotic function of p53. - Samuels-Lev, Y; O'Connor, D; Bergamaschi, D; Trigiante, G; Hsieh, J; Zhong, S; Campargue, I; Naumovski, L; Crook, T; Lu, X (2001)
We identified a family of proteins termed ASPP. ASPP1 is a protein homologous to 53BP2, the C-terminal half of ASPP2. ASPP proteins interact with p53 and specifically enhance p53-induced apoptosis but not cell cycle arrest. Inhibition of endogenous ASPP function suppresses the apoptotic function of endogenous p53 in response to apoptotic stimuli. ASPP enhance the DNA binding and transactivation function of p53 on the promoters of proapoptotic genes in vivo. Two tumor-derived p53 mutants with reduced apoptotic function were defective in cooperating with ASPP in apoptosis induction. The expression of ASPP is frequently downregulated in human breast carcinomas expressing wild-type p53 but not mutant p53. Therefore, ASPP regulate the tumor suppression function of p53 in vivo.